MSME social capital based on e-commerce for business continuity in the era COVID-19 - Hikmah, Lailatul; Prajanti, Sucihatiningsih Dian Wisika; Handoyo, Eko (Universitas Negeri Semarang, 2021)
The study aims to see the extent to which social capital contributes to the sustainability of MSME businesses by utilizing e-commerce in the face of difficult conditions due to the Covid-19 pandemic in Serang City. Departing from the problems related to the difficulty of product marketing during the pandemic and the limited activities of MSMEs. This study uses a qualitative approach, phenomenological research design, with the informant selection technique using purposive random sampling. Data was collected using interviews, observation and documentation. The results of the study indicate that the social and economic conditions of MSMEs are difficult, a significant decrease in income is due to the regional restriction regulations from the government. Having social capital in the form of trust, norms and networks that form mutual trust between MSMEs and consumers. Social capital that contributes significantly is trust and the network of involvement of traders and consumers with e-commerce third parties that facilitate buying and selling transactions. The social structure of commerce, especially its social relations with customers and e-commerce, contributes to the ongoing economic activity. Several aspects that affect the continuity of the MSME business are marketing, production and capital. Trust or trust makes a positive contribution in improving the welfare of traders.